2015
DOI: 10.1007/s11042-015-3111-6
|View full text |Cite|
|
Sign up to set email alerts
|

Local directional gradient pattern: a local descriptor for face recognition

Abstract: In this paper a local pattern descriptor in high order derivative space is proposed for face recognition. The proposed local directional gradient pattern (LDGP) is a 1D local micropattern computed by encoding the relationships between the higher order derivatives of the reference pixel in four distinct directions. The proposed descriptor identifies the relationship between the high order derivatives of the referenced pixel in four different directions to compute the micropattern which corresponds to the local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 24 publications
(19 reference statements)
0
27
0
5
Order By: Relevance
“…LBP is texture feature methodology that takes into account the relationship between the center pixel and neighboring pixels [32]. Variants of LBP algorithm have been employed by many researchers [33][34][35][36][37][38]. Nevertheless, the most important drawbacks of LBP, which uses local spatial features overlooks macro texture information and is sensitive to noise.…”
Section: Introductionmentioning
confidence: 99%
“…LBP is texture feature methodology that takes into account the relationship between the center pixel and neighboring pixels [32]. Variants of LBP algorithm have been employed by many researchers [33][34][35][36][37][38]. Nevertheless, the most important drawbacks of LBP, which uses local spatial features overlooks macro texture information and is sensitive to noise.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the LPOG descriptor with WPCA is robust against illumination, expression, occlusion, pose, time‐lapse variations and low resolution. In another study, local directional gradient pattern (LDGP) is proposed [27]. LDGP computes high order derivatives in four distinct directions for a reference pixel and encodes the relationship between them to obtain the local feature.…”
Section: Introductionmentioning
confidence: 99%
“…There are two kinds of order based descriptors, one using LBP framework in high-order derivative space and another using intensity order among neighboring values for local region matching. Some examples of former approach are LDP [26] and LDGP [34]. Recently, the intensity order based descriptors have been introduced for feature description and applied mainly to the local region matching [40], [41], [42], [43].…”
Section: Introductionmentioning
confidence: 99%